2007
DOI: 10.1086/522608
|View full text |Cite
|
Sign up to set email alerts
|

Acute Hepatitis C in a Contemporary US Cohort: Modes of Acquisition and Factors Influencing Viral Clearance

Abstract: High-risk sexual or iatrogenic exposures may be important contemporary risk factors for HCV infection. The spontaneous viral clearance rate (18%) in this contemporary study was similar to that reported for past studies of transfusion-associated HCV infection. Women were more likely to clear acute HCV infection than men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
115
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(127 citation statements)
references
References 37 publications
10
115
0
2
Order By: Relevance
“…One important outcome is the attainment of a spontaneous resolution of viremia (viral clearance) 37, 38. Viral clearance is estimated to occur in approximately 20% of adults, while children have a slightly greater chance of viral clearance 61, 62, 63. In children with perinatal transmission, 25%‐40% may spontaneously undergo viral clearance, usually by age 2; this has been described as a resolution of neonatal HCV infection 4.…”
Section: Natural History Of Hcv Infection In Children and Adolescentsmentioning
confidence: 99%
“…One important outcome is the attainment of a spontaneous resolution of viremia (viral clearance) 37, 38. Viral clearance is estimated to occur in approximately 20% of adults, while children have a slightly greater chance of viral clearance 61, 62, 63. In children with perinatal transmission, 25%‐40% may spontaneously undergo viral clearance, usually by age 2; this has been described as a resolution of neonatal HCV infection 4.…”
Section: Natural History Of Hcv Infection In Children and Adolescentsmentioning
confidence: 99%
“…Epidemiological studies have shown that 46.2% of all hepatitis C cases are caused by HCV GT1, making GT1 the most prevalent genotype [3]. Even though most of the patients initially do not experience any symptoms, about 75% are not able to spontaneously clear the virus from the organism, and develop a chronic HCV infection [4]. HCV causes progressive liver injury in those patients, which in approximately 16% progress to liver cirrhosis and ultimately in 1-5%, within two decades from acute infection, to hepatocellular carcinoma.…”
Section: Clinical Background Of Hcv Infectionmentioning
confidence: 99%
“…Vertical transmission is also possible and is more likely if the mother is HIV-positive. A more recent trend is the increase in the number of new cases of acute HCV in MSM who are HIV-positive acquired via sexual transmission (8,9).…”
Section: Viral Aetiologiesmentioning
confidence: 99%